Physiological and Anthropometric Determinants of Performance Levels in Professional Futsal - Sekulic, Damir; Pojskic, Haris; Zeljko, Ivan; Pehar, Miran; Modric, Toni; Versic, Sime; Novak, Dario (Frontiers in Psychology, 2021)
There is an evident lack of studies examining the pursuit of excellence in futsal. The aim of this study was to evaluate anthropometric and physiological variables that may contribute to distinguishing among performance levels in professional players and to evaluate correlates of those variables. The participants were 75 male professionals (age = 25.1 ± 5.1 years, body height = 182.3±6.2 cm, body mass = 80.8 ± 10.4 kg), who were divided into performance levels using two criteria: (i) starters (first teams) vs. nonstarters (substitutes), and (ii) top-level players (members of the national team and players who participated in top-level team competition in Europe) vs. high-level players (team players competing at the highest national competitive rank). Variables included anthropometrics (body height and mass, BMI, body fat percentage), generic tests of physiological capacities(5- and 10-meter sprints, CMJ, broadjump, 20-yard test, reactive strength index [RSI]), and futsal-specific fitness tests (kicking speed by dominant and nondominant leg, futsal-specific tests of change of direction speed, and reactive agility [FSRAG] involving/not involving dribbling the ball). Top-level players outperformed high-level players in RSI, broadjump, kicking speed, and FSRAG involving dribbling. Starters achieved better results than nonstarters in fewer variables, including kicking speed and RSI. Body fat percentage negatively influenced FSRAG involving dribbling, and RSI. FSRAG, RSI, and kicking speed were significantly correlated, indicating the similar physiological background of these capacities. The study evidenced the importance of futsal-specific capacities and skills in differentiation of performance levels among professional players. Although significantly correlated with important physiological capacities, anthropometric/body composition indices were not found to be determinants of performance levels, probably due to the high level of the players involved in the study.